DAMPAK PROTEKSIONISME AMERIKA SERIKAT TERHADAP INDONESIA DALAM PERSPEKTIF KONSTRUKTIVISME - Rahmi Fitriyanti; Ammar Judistia; Julia Ulvatmi; Ratu Hanun T.W.A; Siti Nurhaliza (Penerbit Media Wawasan Ilmu, 2023)
The economic protectionism carried out by Trump has had both positive and negative impacts on countries in the world. This paper focuses on the positive impact of US protectionism on its cooperation with Indonesia based on a Constructivism Perspective. The approach used is a qualitative method using secondary data. The US protectionism policy carried out by Trump resulted in the outbreak of a trade war with China throughout the 2017-2020 period, where this succeeded in shocking the international community. During the crisis and world economic tensions, Indonesia managed to overcome a few of these things that it had a positive impact that benefited Indonesia, namely the transfer of several US-imported goods from China to Indonesia and the increasing interest of foreign investors in Indonesia. The analysis is carried out using the ontology of Constructivism which is divided into three, namely, historical, norms, and ideas built by Indonesia for the United States. Indonesia is advised to maintain good relations by building the right nation branding towards the US and China, even though Indonesia is not in favor of either of them.